SMARCA4 (BRG1) Loss of Expression Is a Useful Marker for the Diagnosis of Ovarian Small Cell Carcinoma of the Hypercalcemic Type (Ovarian Rhabdoid Tumor). (September 2015) - Karanian-Philippe, Marie; Velasco, Valérie; Longy, Michel; Floquet, Anne; Arnould, Laurent; Coindre, Jean-Michel; Le Naoures-Méar, Cécile; Averous, Gerlinde; Guyon, Frédéric; MacGrogan, Gaëtan; Croce, Sabrina
<x xml:space="preserve">Abstract</x> Ovarian small cell carcinoma of the hypercalcemic type (SCCOHT)/ovarian rhabdoid tumor is a rare and highly malignant tumor that typically occurs in young women. Up until now the diagnosis has been made on the basis of morphology without any specific immunohistochemical (IHC) markers. However, several authors have shown recently that SCCOHTs are characterized by inactivation of the SMARCA4 gene (encoding the BRG1 protein) resulting in a loss of BRG1 protein expression in IHC. We evaluated BRG1 and INI1 expression in 12 SCCOHTs and in a series of 122 tumors that could mimic SCCOHT morphologically: 9 juvenile granulosa cell tumors, 47 adult granulosa cell tumors, 33 high-grade ovarian serous carcinomas, 9 desmoplastic round cell tumors, 13 Ewing sarcomas (5 from the pelvis and 8 from soft tissues), 1 round cell sarcoma associated with CIC-DUX4 translocation from soft tissue (thigh), 1 case of high-grade endometrial stromal sarcoma of the ovary, and 9 melanomas. Forty-four adult granulosa cell tumors were interpretable by IHC. All 12 SCCOHTs were devoid of BRG1 expression and expressed INI1. All other interpretable 119 tumors showed BRG1 nuclear positivity, with variable staining proportions, ranging from 10% to 100% of positive cells (mean: 77%, median: 80%), variable intensities (weak: 5%, moderate: 37%, strong: 58%), and distributions: diffuse in 82 cases (70%) and heterogenous in 36 cases (30%). BRG1 positivity was heterogenous in desmoplastic round cell tumors and adult granulosa cell tumors. Overall, BRG1 is a useful diagnostic marker in SCCOHT, showing the absence of expression in SCCOHT. Nevertheless, the possible heterogeneity and the variable intensity of this staining warrant caution in the interpretation of BRG1 staining in biopsy specimens.